In Conversation with Sérgio Santimano (Workshop Intermedial Indian Ocean - 2021, 2023)
Pedro Pombo and Elena Brugioni in conversation with Mozambican photographer Sérgio Santimano who visited the Africa Multiple Cluster of Excellence to attend the opening of his exhibition "Goa/Mozambique - Crossed Glances" in Bayreuth. About the artist: Born in Mozambique in 1956 and a native of Goa, Sérgio Santimano contributed significantly as a photographer to the creation of a Mozambican identity after the country's independence in 1975. In 1995, he visited India as an adult and presented an exhibition in Mumbai titled "Caminhos - the long and winding road" with a text by Calane da Silva. His photographs taken in Goa and in the northern provinces of Mozambique (Nacala, Niassa, Cabo Delgado and the island of Mozambique) tell the story of the memories of families living on both sides of the Indian Ocean. Mozambican history testifies of the linkages between the East African coast, Arabia, India. Due to portuguese colonial history, there are very strong linkages between Goa (India) and Mozambique with continuous migrating movements between the two colonies. Identities were evolving in this large contact zone as ongoing processes of dynamic encounters. The work of Sergio Santimano gives an insight into the crossing gazes across the Indian Ocean: “olhares cruzados”, “Blickwechsel”. Recent Exhibitions of Sergio Santimano include “Legado” (2018-2019, Maputo, Goa); “Portas para Goa” (2021, Castelo de Vide)